Involvement of the Left Supramarginal Gyrus in Manipulation Judgment Tasks: Contributions to Theories of Tool Use. (19th June 2017) - Lesourd, Mathieu; Osiurak, François; Navarro, Jordan; Reynaud, Emanuelle
Abstract: Objectives: Two theories of tool use, namely the gesture engram and the technical reasoning theories, make distinct predictions about the involvement of the left inferior parietal lobe (IPL) in manipulation judgement tasks. The objective here is to test these alternative predictions based on previous studies on manipulation judgment tasks using transcranial magnetic stimulations (TMS) targeting the left supramarginal gyrus (SMG).Methods: We review recent TMS studies on manipulation judgement tasks and confront these data with predictions made by both tool use theories.Results: The left SMG is a highly intertwined region, organized following several functionally distinct areas and TMS may have disrupted a cortical network involved in the ability to use tools rather than only one functional area supporting manipulation knowledge. Moreover, manipulation judgement tasks may be impaired following virtual lesions outside the IPL.Conclusions: These data are more in line with the technical reasoning hypothesis, which assumes that the left IPL does not store manipulation knowledge per se . ( JINS, 2017, 23, 685–691)